2016
DOI: 10.1088/1748-9326/11/6/064020
|View full text |Cite
|
Sign up to set email alerts
|

Hotspots of land use change in Europe

Abstract: Assessing changes in the extent and management intensity of land use is crucial to understanding land-system dynamics and their environmental and social outcomes. Yet, changes in the spatial patterns of land management intensity, and thus how they might relate to changes in the extent of land uses, remains unclear for many world regions. We compiled and analyzed high-resolution, spatiallyexplicit land-use change indicators capturing changes in both the extent and management intensity of cropland, grazing land,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
144
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(178 citation statements)
references
References 91 publications
4
144
0
3
Order By: Relevance
“…An increase of pasture land was not observed, but only Heerde (NL) contains significant grassland area and here on the contrary important grassland areas were converted to cropland and urban area. Kuemmerle et al (2016) found that overall changes were moderate, from <1% (grazing land) to 5% (urban area) between 1990-2006, which was similar to our findings (Table 14). Stürck and Verburg (2016) concluded that the selection of scale and used indicators very much influence the findings of such studies.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…An increase of pasture land was not observed, but only Heerde (NL) contains significant grassland area and here on the contrary important grassland areas were converted to cropland and urban area. Kuemmerle et al (2016) found that overall changes were moderate, from <1% (grazing land) to 5% (urban area) between 1990-2006, which was similar to our findings (Table 14). Stürck and Verburg (2016) concluded that the selection of scale and used indicators very much influence the findings of such studies.…”
Section: Discussionsupporting
confidence: 91%
“…Over time an increase in natural habitat is seen in most case studies (Table 16). A study of hotspots of land use change in Europe at NUTS-2 level revealed that most widespread land use change between 1990 and 2006 was cropland decline, followed by forest area expansion and pasture increase (Kuemmerle et al 2016). This trend is confirmed even at smaller spatial scale in this study, where we found that in most cases also the food production potential decreased and timber production increased.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, large areas that had been previously recovered forest and were cultivated or leased for grazing, are now abandoned. This phenomena occurred in particular on the mountains of southern Europe (Kuemmerle et al 2016). This opens an interesting debate in academic circles, on the possible future roles of these forests.…”
Section: Fuelwood Productionmentioning
confidence: 96%